KAJIAN SOTERIOLOGI DALAM FRASE DIBAPTIS DAN DISELAMATKAN DALAM KISAH PARA RASUL 23:8 - Daud Balang; Chris Budi Setiawan (Shema: Jurnal Teologi Injili dan Pendidikan Kristen, 2021)
This paper will discuss several things that are still a problem among Christians themselves, especially regarding Baptism and Salvation. Baptism and salvation are important parts of Christian teaching for believers to understand and teach, but this topic is also a phenomenon that is more frequently discussed among Christians themselves. Differences in church doctrine have often sparked debate with no exception to the issue of baptism and salvation. This paper is intended to look from the biblical point of view in order to have a biblical understanding. For this reason, in this paper it discusses what Peter really meant was the basis of salvation.